Comparison of vibration characteristics of file systems for root canal shaping according to file length - Seong-Jun Park; Se-Hee Park; Kyung-Mo Cho; Hyo-Jin Ji; Eun-Hye Lee; Jin-Woo Kim (Restorative Dentistry & Endodontics)
ObjectivesNo studies have yet assessed vibration characteristics according to endodontic file length. Accordingly, the objective of the present study was to examine the vibration characteristics according to nickel-titanium file length and to compare these characteristics between different file systems.Materials and MethodsA total of 45 root canal models were divided into 3 experimental groups (n = 15 each) based on the file system used (ProTaper Gold [PTG], ProTaper Next, or WaveOne Gold [WOG]). Each experimental group was further divided into 3 subgroups according to file length (21, 25, or 31 mm). An electric motor (X-SMART PLUS) was used in the experiment. For each file system, vibrations generated when using a size 25 file were measured and used to calculate the average vibration acceleration. The differences in vibrations were analyzed using 1-way analysis of variance and the Scheffé post hoc test with a confidence interval of 95%.ResultsIn the PTG file system, significantly lower vibration acceleration was observed when using a 21-mm file than when using a 31-mm file. In the WOG file system, significantly stronger vibration acceleration was observed when using a 31-mm file than when using 21- or 25-mm files. Regardless of the file length, the WOG group exhibited significantly stronger vibration acceleration than the other 2 experimental groups.ConclusionsIn clinical practice, choosing a file with the shortest length possible could help reduce vibrations. Additionally, consideration should be given to vibrations that could be generated when using WOG files with reciprocating motion.